Department-specific Writing Centres linked to Tutorial Programmes - Boughey, John (South African Journal of Higher Education, 2016)
In response to perceived academic unpreparedness on the part of first year students, in the second semester of 2010 a number of departments in the Faculties of Arts, Commerce, Administration & Law (CAL), and Science at the University of Zululand (Unizulu) opted to use the Department of Higher Education & Training’s Teaching Development Grant to implement a model of academic support comprising a tutorial component (one hour per week) and assistance with academic writing (on demand and by appointment) – preferably in a dedicated physical space designated as a departmental Tutorial Room-cum-Writing Centre. The support was to be given by senior students in the department, who functioned both as ‘tutors’ and as ‘writing respondents’. These activities were overseen by the lecturer(s) responsible for the first year programme. Capacity-building for staff and tutors was provided by Academic Development (AD). This article first describes the policy context of the University of Zululand, and then outlines the theory underlying the model and the process of gaining initial ‘buy-in’. Drawing on feedback received from academic staff, student tutors and students, the article goes on to document the unfolding implementation of the model and its impact on teaching and learning. The article concludes with a set of recommendations for continued implementation in 2011, in the belief that combination of tutorials and assistance with academic writing constitute a useful contribution to the promotion of quality higher education.